Caloric restriction mimetics chlorogenic acid and fisetin as potential autophagy inducers targeting ATG101 - Apoorv Sharma; Indu Kumari; Asimul Islam; Hridayesh Prakash; Amresh Prakash; Vijay Kumar (Biochemistry and Biophysics Reports, 2025)
Autophagy is an important cytoprotective process impaired in neurodegenerative diseases such as Alzheimer's disease. The initiation process is mediated by the protein kinase Unc-51-like kinase 1 (ULK1) complex. ATG101, a cytosolic protein, plays a pivotal role in initiating autophagy as a component of the ULK complex in mammalian cells. It is important to understand the regulatory processes of individual autophagy components under different conditions for the development of therapeutic interventions. The caloric restriction mimetics (CRMs) such as chlorogenic acid (CGA) and fisetin mimic the healthy outcomes of caloric restriction without decreasing caloric consumption, constituting promising therapeutic candidates for neuroprotection. We explored the ATG101 interactions of CGA and fisetin in this work. Molecular docking and molecular dynamics (MD) simulations were used to investigate the interactions of these CRMs with ATG101, evaluating binding stability and dynamics. To confirm these interactions, we conducted quantitative real-time PCR (qRT-PCR) in differentiated SHSY5Y cells, analyzing the effect of CGA and fisetin on ATG101 gene expression. Our results indicated that fisetin forms a more stable complex with ATG101 compared to CGA. Yet, at the transcriptional level, both CRMs stimulate the mRNA level of ATG101. Therefore, these CRMs can be responsible for their potential as autophagy inducers. These findings offer significant insights into the molecular processes through which CRMs may improve neurodegenerative diseases by triggering autophagy.